PENGEMBANGAN PANDUAN PEMBELAJARAN APRESIASI SASTRA BERBASIS TEORI RESEPSI UNTUK GURU SMA - Ari Suryawati Secio Chaesar; Maman Suryaman (BAHASTRA, 2018)
This research and development has purpose to describe the findings of the guidance of material book product development of literature appreciation learning based on reception theory for Senior High School teachers; to describe the validity of the book by expert judgments; and to describe the reliability by teachers based on content, service, language, and graphic aspects. The research uses Borg and Gall model through the modified stages: preliminary, product development planning, product development, expert validity test, product revising, and product trial run. The validity results from content experts shows the content reliability gaining score 4.17, categorized very well; service reliability gaining score 4.38, categorized very well; and language reliability gaining score 4.25, categorized very well. The product validity from graphic expert gains score of 4.14, categorized very well. The product reliability gained from 25 Indonesian language teachers shows the content, gaining 4.32, categorized very well; service reliability gaining score 4.38, categorized very well; language reliability gaining score 4.37, categorized very well; and graphic reliability gaining score 4.41, categorized very well. The development was the useful form of innovation to maximize the learning process in schools.Â